Grain boundary dominated ion migration in polycrystalline organic–inorganic halide perovskite films. Issue 5 (8th April 2016) - Shao, Yuchuan; Fang, Yanjun; Li, Tao; Wang, Qi; Dong, Qingfeng; Deng, Yehao; Yuan, Yongbo; Wei, Haotong; Wang, Meiyu; Gruverman, Alexei; Shield, Jeffery; Huang, Jinsong
Abstract : Grain boundaries have been demonstrated as the dominating ion migration channels in polycrystalline organic–inorganic halide perovskite films. Abstract : The efficiency of perovskite solar cells is approaching that of single-crystalline silicon solar cells despite the presence of a large grain boundary (GB) area in the polycrystalline thin films. Here, by using a combination of nanoscopic and macroscopic level measurements, we show that ion migration in polycrystalline perovskites dominates through GBs. Atomic force microscopy measurements reveal much stronger hysteresis both for photocurrent and dark-current at the GBs than on the grain interiors, which can be explained by faster ion migration at the GBs. The dramatically enhanced ion migration results in the redistribution of ions along the GBs after electric poling, in contrast to the intact grain area. The perovskite single-crystal devices without GBs show negligible current hysteresis and no ion-migration signal. The discovery of dominating ion migration through GBs in perovskites can lead to broad applications in many types of devices including photovoltaics, memristors, and ion batteries.